The gospel of good will as revealed in contemporary scriptures - Hyde, William De Witt (The Lyman Beecher lectures on preaching at the Yale school of religion for 1916, 1916)
The gospel of good will: Christ's expectation of men -- Falling short of good will: The meanness of sin -- Restoration to good will: Repentance and forgiveness -- Good will in secular vocations: Service -- The cost of good will: Sacrifice -- By-products of good will: The Christian virtues -- Good will in society: Reform -- Fellowship in good will: The Church.